Membangun Gerakan Sadar dan Tertib Administrasi Kependudukan dan Pencatatan Sipil - Mirlana, Dendy Eta; Sunarso, Sunarso; Halim, Abdul; Sahuti, Abu Kusno; Widyaningsih, Aulia Zalzabela; Khasanah, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
In order to organize a good and integrated population administration system, accurate and valid population data is needed because population data can be used as a basis for development planning, both short and long term. There are still many people who are not aware of the importance of population documents and the accuracy of population data for purposes of administering public services, and there are still many people who do not understand population administration service procedures. Regarding community conditions like this, lecturers and students at Merdeka University, Ponorogo Regency Campus are trying to participate in community service activities in socializing conscious and orderly population administration movements in the Ponorogo Regency area. The aim of this activity is to increase public knowledge and awareness regarding the importance of population documents in everyday life, the public understands the procedures for processing population administration documents and the public is more orderly in reporting if there are changes to their population data. This method of implementing community service uses a participatory method, namely through lectures, discussions and consultations, which allows the service team to interact, communicate intensively, discuss and ask questions directly with the community. By building public awareness of orderly administration, especially population administration, population data can become more accurate and valid so that data in the Population Administration Information System becomes more perfect.